Children’s online learning during COVID-19 pandemic: experiences and satisfaction encountered by Indian parents - Hepsi Bai Joseph; Sandhiya Kuppuswamy; Asha Prabhakar Shetty (Journal of Ideas in Health, 2021)
Background: Online learning by children is pressure for children as well as parents. The Covid-19 lockdown was ended up putting much stress on parents in India. The current study aimed to assess the parental experience and satisfaction on online learning for their children during Covid -19 pandemic lockdown.